Genome-Wide Analysis and Polymorphism Evaluation of Microsatellites Involved in Photoperiodic Flowering-time Genes in Kenaf (Hibiscus Cannabinus L.). Issue 14 (28th October 2022) - Xu, Yi; Li, Dongxu; Afzal, Muhammad Zohaib; Yao, Jiayu; Xu, Jiantang; Lin, Lihui; Qi, Jianmin; Zhang, Liwu
ABSTRACT: Kenaf ( Hibiscus cannabinus L.) is one of the most important crops, which is grown for natural fiber production. However, the deficiency of SSR markers limits the genetic improvement of kenaf. In this study, SSRs (simple sequence repeats) were identified from the reference genome and coding sequence (CDS) of Fuhong952, a sequenced variety of kenaf. SSR loci were mined using the Seiners 2.0 software and the characteristics of SSR loci were analyzed. A total of 301, 505 and 14, 269 SSRs with an overall density of 279.70 SSRs/Mb and 182.70 SSRs/Mb were identified from whole-genome and CDS, respectively. 12bp was the predominant repeat in the entire genome and CDS, trinucleotide repeats were the most abundant among both types of sequences. For different SSR repeat types, the SSR frequency decreased dramatically as repeat times increased. AT was the most frequent single motif across the entire genome, while AG was the most abundant motif in CDS. The homologous genes in kenaf were obtained from the 71 genes associated with photoperiodic flowering-time. As such, 115 primer pairs were designed and synthesized using these homologous genes in kenaf. The amplification of 108 pairs revealed stable and clear bands, and two pair of primers located in HcFCA and HcVIN3 were significantly associated with photoperiodic flowering-time using one-way ANOVA and regression analysis. The detailed results of the SSR markers in this study provides valuable information about the frequency distribution of SSRs in the whole genome and will expedite genomic research for improvement in kenaf.